Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan - Bagas Arif Prabaswara; Dhea Puspita Sari; Raffi Eka Nugraha; Indah Rizki Maulia (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Human resources are the main element that must be maintained in terms of quality within a company. Good human resources are assessed based on the results of employee performance. Leadership style and motivation are one of the factors that can affect the level of employee performance. This study aims to determine the influence of leadership style (X1) and work motivation (X2), both directly or simultaneously, on employee performance (Y). The method of writing this article is the Literature Review method, sourced from online media such as Google Scholar, Mendeley, and other academic online media. Based on the results of the research, leadership style (X1) and work motivation (X2) have a significant influence on performance (Y).